Perancangan Alat Monitoring Error Current Transformer (AMOR CT) Menggunakan Arduino Mega 2560 dan Cayenne IoT - Taufik Hidayat; Hansi Effendi (Jurnal Teknik Elektro Indonesia, 2021)
Current Transformer (CT) is an important component that functions as a tool to regulate the amount of current that enters the kWh Meter on a 3-phase indirect measurement customer. To ensure the accuracy of measuring instruments, especially CT, it is necessary to check whether the installed CT still meets the standards. Current Transformer error (CT error) is the difference between the measured value on the secondary side and the actual value on the primary side of a CT measurement. This final project aims to design a tool that is able to provide information and record CT error value measurement data in real time and display it on the Cayenne IoT. This final project uses Arduino Mega 2560 with PZEM 004T module as a current sensor, GSM 800L module for Arduino connection with Cayenne IoT. Cayenne IoT is used to visualize the data so that the CT measurement conditions can be monitored. Each PZEM 004T will read current changes and the data will be processed by Arduino Mega 2560 and then sent to Cayenne Iot for display, making monitoring and data retrieval easy. After making and testing the tool, it was found that the design tool was able to send measurement results to the Cayenne IoT and was able to provide real-time information and record CT error value measurement data installed on the customer's electrical panel for evaluation materials with the expected measurement results with direct measurements contained in 0% - 0.3% difference in AMOR CT readings with Ampere Tang.